TINDAKAN KHUSUS BERUPA PEMBAKARAN DAN/ATAU PENENGGELAMAN KAPAL IKAN ASING YANG MELAKUKAN TINDAK PIDANA PERIKANAN DI ZONA EKONOMI EKSKLUSIF INDONESIA - Mangisi Simanjuntak (Fakultas Hukum Universitas Kristen Indonesia, 2017)
Abstract In the research shows that the rampant illegal fishing causes Indonesia to lose its fish resources around Rp 30 trillion per year. Fishing vessels caught for committing a criminal offense are processed under applicable law. The legal process took so long that many fishing vessels that were moored at the base were damaged while the finished ones and the ship’s court had been auctioned off but in reality the fishing vessel was back to its owner.For the settlement of both the necessary special measures of burning and / or drowning with sufficient preliminary evidence and approval of the chairman of the district court as stated in Article 69 paragraph (1), (4) and Article 76A of Law Number 45 Year 2009 concerning Fisheries . Countries whose fishing boats conduct illegal fishing protest against such special measures and how prevention efforts for fishery crimes can be minimized? Specific acts for fishery crimes committed in ZEE Indonesia shall not be made as they are contrary to Article 73 paragraph (2), Article 194, Article 309 of the UN Convention 1982 (Unclos 1982) and Article 15 of Law Number 5 Year 1983 on ZEE Indonesia And Article 104 Paragraph (1) of Law Number 31 Year 2004 concerning Fisheries that permit fishing vessels to be exempted by a ransom of adequate security deposit, by way of a court application. Such application shall be filed by the ship’s captain and / or his or her representative.If the court rejects the aforementioned redemption application then the legal proceedings will continue and if the ship is not redeemed, the legal proceedings continue and there should also be a statement signed by the ship’s captain or the representative of his country stating that his fishing vessel will not be redeemed. Burning and / or The drowning of foreign fishing vessels committing fishery crimes in ZEE Indonesia can only be done if the case has a permanent legal force. To engage in the burning and / or drowning of foreign fishing vessels committing a fishery crime in ZEE Indonesia requires a new legal norm as described above. Keywords: Special Measures of Combustion and/or Drowning of Foreign Fishing Vessels